(untitled) (FULafia Journal of Science and Technology, 2024)
Contamination of Agricultural commodities by moulds poses significant challenges due to conducive climatic conditions. Mycotoxins produced by moulds like Aspergillus, Penicillium, and Fusarium present health risks and economic losses. Traditional control measures such as the use of fungicides have drawbacks, necessitating the exploration of eco-friendly alternatives. One such alternatives is the use of Chitosan, a biopolymer derived from chitin found in crustacean exoskeletons. This study evaluated the efficacy of chitosan synthesized from shrimp shells in inhibiting the growth of Aspergillus niger, a common food borne mould of oil seeds such as Sesame. Synthesized Chitosan was characterized using FTIR spectroscopy, UV-visible spectroscopy, and the degree of deacetylation was determined. FTIR analysis showed characteristic absorption peaks ranging from 3911.77 cm-1 to 794.70 cm-1, with higher wave numbers corresponding to stretching vibrations of the C-H, O-H, and N-H bonds functional groups. UV-visible spectroscopy displayed an absorbance peak at 232 nm with an absorbance value of 2.15. The degree of deacetylation of synthesized chitosan was determined to be 98.99%. In vitro experiments showed a concentration-dependent inhibition of A. niger growth by shrimp shell synthesized chitosan. The highest level of inhibition was seen at day 3 with 0.75mg/ml (50%) and 1.0mg/ml (52.1%), meaning the higher the concentration of shrimp shell synthesized chitosan the higher the inhibition. Results suggest chitosan as a potential anti-fungal agent for food preservation and agricultural protection against mould contamination and mitigate post harvest losses and ensure food safety.